Noninvasive Left Ventricular Myocardial Work in Patients with Chronic Aortic Regurgitation and Preserved Left Ventricular Ejection Fraction - Meucci Maria Chiara; Butcher Steele C; Galloo Xavier; van der Velde Enno T; Marsan Nina Ajmone; Bax Jeroen J; Delgado Victoria (Elsevier Inc., 2022)
Background
Left ventricular (LV) global longitudinal strain (GLS) has been proposed as a sensitive marker of myocardial damage in patients with chronic severe aortic regurgitation (AR) and preserved LV ejection fraction (LVEF). However, LV GLS does not take into account the afterload. Noninvasive LV myocardial work is a novel parameter of LV myocardial performance, which integrates measurements of myocardial deformation and noninvasive blood pressure (afterload). The aims of this study were (1) to assess noninvasive LV myocardial work in patients with chronic AR and preserved LVEF and its correlation with other echocardiographic parameters, (2) to evaluate changes of LV myocardial work after aortic valve replacement or repair (AVR), and (3) to assess the relationship between LV myocardial work and postoperative LV reverse remodeling.
Methods
Fifty-seven patients (53 ± 16 years; 67% men) with moderate or severe chronic AR and preserved LVEF treated by AVR were included. Noninvasive LV myocardial work indices were measured at baseline and postoperatively (between 2 and 12 months after surgery) and compared with previously reported normal reference ranges.
Results
Based on normal reference values, patients with chronic AR and preserved LVEF had preserved or increased values of LV global work index (GWI; 82% and 18%, respectively) and LV global constructive work (GCW; 74% and 25%, respectively) and preserved LV global work efficiency (GWE). Left ventricular GWI and GCW showed a positive correlation with markers of AR severity and parameters of LV systolic function. Left ventricular GWI, GCW, and GWE decreased after AVR (P < .001), without changes in LV global wasted work (P = .28). The postoperative impairment of LV GWI, observed in 28% of patients, was closely associated with reduced LV reverse remodeling.
Conclusions
Noninvasive myocardial work may allow better understanding of myocardial function and energetics than afterload-dependent echocardiographic parameters in chronic AR with preserved LVEF.